Determining parameters of electromagnetic radiation for energoinformational disinfection of wool in its pretreatment - Kosulina, Nataliaya; Cherenkov, Aleksandr; Pirotti, Evgenij; Moroz, Sergey; Chorna, Mariya (Eastern-European Journal of Enterprise Technologies, 2017)
The paper is devoted to solution of theoretical and experimental problems in development of electromagnetic (EM) technology in the millimeter wavelength range for disinfection and warming of baled wool during its processing. Sheared wool is an environment well fit for existence of a variety of microorganisms. It was established that 1 kg of wool contains 400 to 7000 million bacteria. This often leads to workers infection with pathogens of brucellosis, myterosis, glanders, toxicoplasmosis, ku-reketmosis, leptospirosis, anthrax and plague. When storing unwashed wool, especially at low temperatures, its compression and fat hardening take place. Fat softens and the rune easily unfolds at temperatures of 25...30 °C. This improves sorting quality and preserves natural wool properties. In this regard, the work studied the regularities of influence of EM energy in the millimeter wavelength range on the pathogenic microorganisms existing in wool. As a result of the studies, a range of changes in the biotropic EMF parameters was determined for destruction of microorganisms. The performed calculations have shown that the biotropic parameters of electromagnetic field include frequency range of 35.3...36.3 GHz; power flux density of 1.25 mW/cm2, exposure time of 2·103 s. Theoretical analysis of the model of warming up baled wool have shown that the temperature rise up to 24...40 °C is possible when wool is exposed to EMF with the following parameters (frequency; power flux density; exposure time): 36 GHz; 1.25...1.5 mW/cm2; 120...180 s. It was established that when wool was exposed to an EMF with certain biotropic parameters, wool breaking load increased by 200...300 cN and relative strength increased by 2...3 cN/tex in comparison with the control runs. The study results make it possible to create an environmentally friendly and efficient technology for primary wool processing by EM energy.